Genetic diversity and path analysis in tomato (Solanum lycopersicum L.) - Buckseth, Tanuja; Sharma, Manish K; Thakur, KS (Vegetable Science, 2012)
Tomato (Solanum lycopersicum L.) occupies the prime position among different vegetables and is an important vegetable cultivated in India. The present trend in crop improvement programmes is the development of hybrid cultivars to boost the productivity and profitability of farmers. To meet all the requirements of successful hybrids, it is neccessary to be familiar with the detailed genetic makeup of the selected material to be used in hybrid breeding. Genetic variability among the parents is a prerequisite to develop new cultivar and select better segregants for various economic characters. Knowledge of correlations is equally important for simultaneous and/ or indirect improvement of characters that are difficult to quantify especially for those traits, which exhibit low heritability. Therefore, it is essential to make preliminary investigation of the characters of the lines to be used for the development of superior hybrids/varieties. In the view of above, present investigation were undertaken to study the genetic variability, correlation among different quantitative and qualitative traits and path analysis in tomato genotypes to facilitate the selection of suitable superior genotypes for development of new varieties/ hybrids using standard breeding programme.